Implementasi Guru Dalam Video Pembelajaran Melalui Aplikasi Bandicam Pada Sarana Pembelajaran Google Classroom - Hilyah Ashoumi; Ika Dewi Mashitoh (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2021)
The purpose of this study is to answer the pandemic problem in MTsN 9 Jombang.With the help of data packages from the Ministry of Education to students and teachers, regulations related to online learning obligations are helped even though media problems and creative limitations in applying media are still haunting, young teachers who are creative in applying media are the potential of MTsN 9 Jombang.Especially in Arabic subjects that allow teachers to use learning video media to make the learning process easier.This research method uses development research which is usually abbreviated to R&D.This study adopted a model developed by Borg and Gall and the development procedures in this study include several stages (1) of potential and problem analysis, (2) data collection, (3) product design, (4) design validation, (5) design improvement, (6) product trials, (7) product revisions.The study was declared worthy with a percentage of eligibility from material experts of 74.05% and media experts of 77.14% with excellent student response with a percentage of 82.04%.